2013
DOI: 10.1097/igc.0b013e31827a2003
|View full text |Cite
|
Sign up to set email alerts
|

Toll-Like Receptors 7, 8, and 9 Expression and Function in Primary Human Cervical Cancer Langerhans Cells: Evidence of Anergy

Abstract: Cervical tumor LCs lacked TLR9 expression and were functionally anergic to all the 3: TLR7, TLR8, and TLR9 ligands, which may play a crucial role in immune tolerance. The exact location of block(s) in TLR7 and TLR8 signaling needs to be investigated, which would have important immunotherapeutic implications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 24 publications
1
10
0
Order By: Relevance
“…For example, E6 oncoprotein induces significant downregulation of β‐interferon (IFN) in keratinocytes, and the reduction in the expression of α‐IFN response genes has been attributed to the presence of E7 [Nees et al, ; Zhou et al, ]. Furthermore, early oncoproteins are associated with diminished levels of molecules necessary for antigen processing and presentation, such as Toll‐like receptor‐9 (TLR9) and the transporter associated with antigen processing (TAP) [Kumar et al, ; Zhou et al, ]. Additionally, HPV persistence and cervical lesion progression are commonly associated with the failure to mount HPV‐specific type 1 T‐helper and cytotoxic T‐cell responses and characterized by changes in the cytokine expression profile from a Th1 to Th2 response and by the increased expression of Interleukin‐10 (IL10) [Woo et al, ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, E6 oncoprotein induces significant downregulation of β‐interferon (IFN) in keratinocytes, and the reduction in the expression of α‐IFN response genes has been attributed to the presence of E7 [Nees et al, ; Zhou et al, ]. Furthermore, early oncoproteins are associated with diminished levels of molecules necessary for antigen processing and presentation, such as Toll‐like receptor‐9 (TLR9) and the transporter associated with antigen processing (TAP) [Kumar et al, ; Zhou et al, ]. Additionally, HPV persistence and cervical lesion progression are commonly associated with the failure to mount HPV‐specific type 1 T‐helper and cytotoxic T‐cell responses and characterized by changes in the cytokine expression profile from a Th1 to Th2 response and by the increased expression of Interleukin‐10 (IL10) [Woo et al, ].…”
Section: Introductionmentioning
confidence: 99%
“…[17,18] Some TLRs in tumor cells indeed biologically impact on tumor cell growth and survival. For example, TLR5 is highly expressed in breast carcinoma and gastric carcinoma cells, and TLR5 signaling inhibits breast cancer growth, but promotes the proliferation of gastric cancer cells.…”
Section: Resultsmentioning
confidence: 99%
“…A recent report found that Bcl-2, as an inhibitor of apoptosis, had prognostic value in classical Hodgkin lymphoma 20. The predominant regulator of tumor angiogenesis is VEGF, which has become an important target in the development of novel anti-tumor strategies 21-22, although the clinical effectiveness of these new strategies remains to be seen 23. The increased VEGF and Bcl-2 expression reported here suggests that future therapeutic approaches targeting on angiogenesis can be used in cervical cancer patients.…”
Section: Discussionmentioning
confidence: 99%